A concerned clinical situation in pediatric cases: Acute myopericarditis, experience of a center from Anatolia (Annals of Medical Research, 2021)
Aim: Myopericarditis/Perimyocarditis is an inflammation in the heart muscle. There is an increase in cardiac biochemical markerswith echocardiographic (ECHO) and/or electrocardiographic (ECG) changes in patients. We aimed to investigate the demographic,clinical, laboratory and imaging features and follow-up results of patients diagnosed with acute myopericarditis in our clinic.Materials and Methods: In this study, demographic and laboratory data and physical examination findings of 15 pediatric patientsdiagnosed with myopericarditis between December 2017-September 2020 were retrospectively recorded.Results: Five (33.3%) of the patients were girls, 10 (66.6%) were boys. The first presentation complaint was chest pain in 11 (73.3%)patients, palpitations in two (13.3%) patients, respiratory distress, abdominal pain and vomiting in two (13.3%) patients. Troponinvalues were increased in all cases. N-terminal prohormone brain natriuretic peptide (NT-ProBNP) level was>100 pg/ml in sevenpatients. In treatment, nine patients received ibuprofen, and three patients received inotrope and anticongestive therapy support aswell as intravenous immunoglobulin (IVIG). In the follow-up, heart functions normalized within four months in all cases.Conclusion: Myopericarditis should be considered especially in adolescent boys who present with complaints such as chestpain, palpitations, respiratory distress, and cardiac enzyme elevation and ECG changes. Although the prognosis is good in mostof myopericarditis cases, the risk of morbidity may be high in patients with high initial cardiac enzyme values, delayed cardiacenzyme return to normal, and systolic dysfunction on ECHO, so long-term follow-up of these patients should be done by pediatriccardiologists.